2013
DOI: 10.7567/jjap.52.04cb09
|View full text |Cite
|
Sign up to set email alerts
|

Reductant-Assisted Self-Assembly with Cu/Sn Microbump for Three-Dimensional Heterogeneous Integration

Abstract: To establish liquid-assisted assembly processes applicable to heterogeneous system integrations, we present flip-chip self-assembly of dies with Cu/Sn microbumps using the difference in droplet wetting between hydrophilic and hydrophobic areas. Flip-chip self-assembly is assisted by a water-soluble flux that has high surface tension comparable to that of pure water and contains an additive of a reducing agent for metal oxides. Control of the additive concentration in the flux provides high wettability contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The flux diluted in water can remove the oxidized thin surface while self-assembled. We have demonstrated Cu/Sn microbump bonding with low contact resistances (8), (9). The second one is the use of NCF (non-conductive film) that is typically laminated on bumped wafers prior to saw dicing.…”
Section: Self-assembly Based Multichip-to-wafer Bonding Technologiesmentioning
confidence: 99%
“…The flux diluted in water can remove the oxidized thin surface while self-assembled. We have demonstrated Cu/Sn microbump bonding with low contact resistances (8), (9). The second one is the use of NCF (non-conductive film) that is typically laminated on bumped wafers prior to saw dicing.…”
Section: Self-assembly Based Multichip-to-wafer Bonding Technologiesmentioning
confidence: 99%
“…Optical path for intra-chip, chip-to-chip, and on-board, VCSEL, PD, optical TSV, lens parts, and optical path conversion components transmission in high-performance computing systems, highend servers, and data center networks. [34][35][36] However, compared with other optical devices such as photodiodes and optical modulators, light-emitting device arrays such as LDs and VCSELs cannot be monolithically integrated owing to their low process compatibility with Si devices. 37) Therefore, the emitting device arrays require high-precision massively parallel assembly procedures.…”
Section: Optical Interconnectionmentioning
confidence: 99%
“…So far, most of the self-assembly works have dealt with highly symmetric square, polygonal, circular, or low-aspect-ratio rectangular chips. 10,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Broesch et al have reported the effects of chip geometries on restoring force and torque by extending the symmetric squares to rectangles with high aspect ratios using simulation software. 38) However, only a few papers on liquid-mediated self-assembly even with symmetric square chips have described their alignment accuracies in detail.…”
Section: Optical Interconnectionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported precise flip-chip selfassembly and microbump interconnections using KGDs with fine-pitch In/Au bumps [12][13][14] and with Cu/Sn bumps [15,16], respectively. This paper proposes a new flip-chip selfassembly method using KGDs covered with NCFs to realize high-throughput and highly-reliable microbump interconnections for advanced direct multichip-to-wafer 3D integration.…”
Section: Introductionmentioning
confidence: 99%